Uji Potensi Hasil Beberapa Mutan Padi Beras Hitam Generasi Ketiga (M3) Hasil Induksi Mutasi: Yield Potential Evaluation of Several Third-Generation (M3) Black Rice Mutants Resulting from Mutation Induction - Ni Wayan Sri Suliartini; Muslim Ashari; Lestari Ujianto; I Gusti Putu Muliarta Aryana; I Wayan Sudika (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
This study aims to determine the yield potential of several third-generation (M3) black rice mutant strains resulting from mutation induction. The experiment was conducted in a paddy field located in Saribaye Village, Lingsar District, West Lombok Regency, West Nusa Tenggara, from March to November 2022. The experimental design used was a Randomized Block Design (RBD) with nine rice genotypes as treatments, repeated three times. These consisted of seven mutant strains of black rice and two controls, namely the Baas Selem and Inpago Unram varieties. The data were analyzed using Analysis of Variance at a significance level of 5%. In case of significant differences among treatments, further analysis was conducted using the Duncan Multiple Range Test (DMRT) at a significance level of 5%. Based on the research findings, two genotypes of third-generation black rice mutants (M3) resulting from mutation induction were identified. These genotypes, namely D3G46(13) with a yield potential of 5.64 tons/ha and D3G62(19) with a yield potential of 5.84 tons/ha, exhibited higher yield potential compared to their parental strains. However, both of these genotypes have not yet achieved or surpassed the yield potential of the control treatment, which is the Inpago Unram with a yield potential of 8.17 tons/ha.